Oligomerization and toxicity of Aß fusion proteins - Caine, J.; Bharadwaj, Prashant; Sankovich, S.; Ciccotosto, G.; Streltsov, V.; Varghese, J. (2011)
This study has found that the Maltose binding protein Aß42 fusion protein (MBP-Aß42) forms soluble oligomers while the shorter MBP-Aß16 fusion and control MBP did not. MBP-Aß42, but neither MBP-Aß16 nor control MBP, was toxic in a dose-dependent manner in both yeast and primary cortical neuronal cells. This study demonstrates the potential utility of MBP-Aß42 as a reagent for drug screening assays in yeast and neuronal cell cultures and as a candidate for further Aß42 characterization. © 2011 .